2017
DOI: 10.1016/j.compositesb.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale failure analysis of periodic masonry structures with traditional and fiber-reinforced mortar joints

Abstract: In this paper, a novel adaptive multiscale model is proposed for accurately predicting the nonlinear mechanical response of periodic brick masonry due to crack initiation and propagation under general in-plane loading histories. Such a model relies on a two-level domain decomposition technique, used in conjunction with an adaptive strategy able to automatically zoom-in the zones incipiently affected by damage localization, with the aim of reducing the typically high computational effort associated with fully m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Application of the proposed integrated fracture approach to other quasi‐brittle materials, as mortars, rocks, fiber‐reinforced or particle‐reinforced composites, some types of ceramics, masonries, etc. In particular, the in‐plane response of masonry structures (of both unreinforced and reinforced type) could be easily predicted by the adopted DIM, allowing different failure mechanisms of individual phases (eg, mortar and bricks) to be correctly captured, involving a priori unknown complex crack patterns, whose influence of the overall nonlinear mechanical behavior has been extensively demonstrated in the literature (see, for instance,).…”
Section: Discussionmentioning
confidence: 99%
“…Application of the proposed integrated fracture approach to other quasi‐brittle materials, as mortars, rocks, fiber‐reinforced or particle‐reinforced composites, some types of ceramics, masonries, etc. In particular, the in‐plane response of masonry structures (of both unreinforced and reinforced type) could be easily predicted by the adopted DIM, allowing different failure mechanisms of individual phases (eg, mortar and bricks) to be correctly captured, involving a priori unknown complex crack patterns, whose influence of the overall nonlinear mechanical behavior has been extensively demonstrated in the literature (see, for instance,).…”
Section: Discussionmentioning
confidence: 99%
“…The variational formulation for the equilibrium problem at the microscopic scale is rather classic and, thus, not reported here for the sake of brevity. However, with the aim to find more theoretical and computational details, the reader is referred to the works [13,16,17], in which this formulation is embedded within a more general multiscale framework. In this paper the following mixed-mode TSL of the type   = T T  , proposed by [50], is chosen (see Fig.…”
Section: Heterogeneous Fem Analysismentioning
confidence: 99%
“…These models are often derived by considering only two material scales: a micro-scale where, after deducing the mechanical properties of the components, preferably through experimental tests, a material representative volume element (RVE) is defined and a macro-scale continuum model, is obtained by performing a homogenization procedure in most cases based on the solution of notable boundary conditions problems for the RVE. Among these approaches, both concurrent and semiconcurrent multiscale models have been proposed in the literature for masonry-like materials, the first ones referring to a strong coupling between the micro-and macro-levels [13][14][15][16], the latter ones, often referred to as computational homogenization models, characterized by an only weak (although two-way) coupling between them [17][18][19][20]. Most of the existing approaches are devoted to the mechanical behavior of periodic (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous research paper developed in the masonry structures and related to the fibre. Samuel et al investigated these properties make fibre reinforced polymer materials, reinforced and unreinforced masonry structures are attractive for rehabilitating and strengthening [1], FRP materials are using of masonry structures to increase the shear and ductility and flexural strength [2].Fabrizio Greco et al have studied the microscopically first failure surfaces takes higher-order deformation effects [3], a sensitivity analysis is carried out on the shear wall sample the different input numerical parameters [4].Ornela Lalaj et al have studied the control specimen compared to increase in shear strength capacity up to 412%, mortar plaster are ferrocement, and polypropylene [5], the stiffness change and failure mode are more varied for strengthening techniques [6].Deniz Ucer et.al. The compression test of brick and mortar separately as well as wall prisms indicated that their strength was still higher than standard limits these wall pieces could be reused under appropriate conditions [7], the bed mortar was tested under shear loads to understand bed joints reliability [8].…”
Section: Introductionmentioning
confidence: 99%